Pajanan Partikulat Debu Kapur dan Faktor Risiko Pekerja dengan Kejadian ISPA: Sebuah Literature Review - Mirza Fathan Fuadi; Onny Setiani; Yusniar Hanani Darundiati (POLTEKKES KEMENKES MANADO, 2021)
Limestone mining is an industry that produces pollutants in the air. The pollutants produced from the lime mining industry are dust and gas particles. The resulting lime dust can harm the health of workers. ARI is a respiratory disease that attacks lime mining workers. ARI does not only occur due to exposure to lime dust, there are several risk factors for workers that can cause ARDs. This study aims to determine the exposure to lime dust and the risk factors for workers with the incidence of ARI. This research was conducted using the literature review method with a sample size of 16 journals. The results showed that 80% of the variables studied were significant or had a relationship with the incidence of ARI. From the review of the article, it is known that there is a period of work, use of PPE, age, history of disease, and smoking habits. The most dominant risk factors that have a significant relationship with the incidence of ARI are the working period variable and the use of PPE.